THE EFFECT OF COMPUTATIONAL THINKING-BASED E-LKM ON IMPROVING LEARNING OUTCOMES RELATED TO NUMERACY LITERACY SKILLS AMONG ELEMENTARY SCHOOL STUDENTS - Farhan Iqbal Pratama; Sri Sumartiningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The study aims to analyze the effect of computational thinking-based electronic student worksheets (E-LKM) on improving cognitive learning outcomes related to elementary students’ numeracy literacy skills. This research employed a quantitative, pre-experimental design with a one-group pretest-posttest method. The sample consisted of 22 fifth-grade students. Data were collected through numeracy literacy tests, while data analysis was conducted using the N-Gain test and the Wilcoxon Signed-Rank test. The results showed an increase in the average score from 46.02 to 57.61, with a significance value of 0.000 (<0.05). These findings indicate that computational thinking-based E-LKM has a significant effect on improving students’ numeracy literacy skills and cognitive learning outcomes.